33.9k views
3 votes
Question 7 of 25

If F(x) = 2x-5 and G(X) = x2 + 1, what is G(F(x))?
O A. 4x2 + 26
O B. 2x2 + 2x-5
O C. 4x2 - 20x + 26
O D. 2x3-5

User Theodosia
by
5.7k points

1 Answer

3 votes

Answer: C

Explanation:

G(F(x)) means F(x) is being plugged into every x in G(x). Since we are given the G(x) and F(x) functions, we can directly plug 2x-5 into x²+1.

G(F(x))=G(2x-5)

G(F(x))=(2x-5)²+1 [use FOIL method to expand (2x-5)²]

G(F(x))=(4x²-10x-10x+25)+1 [combine like terms]

G(F(x))=4x²-20x+26

Now that we have found G(F(x))=4x²-20x+26, we know that the answer is C.

User Marcel Zebrowski
by
5.6k points